Korean Language in Bandung City Public Space: A Landscape Linguistic Study - Sulistiyo, Adhea Tsabitah; Wirza, Yanty; Hermawan, Budi (RETORIKA: Jurnal Ilmu Bahasa, 2025)
This study aims to examine the existence of Korean language in public spaces in Bandung City through a Linguistic Landscape approach. Korean language is increasingly found in various public sectors, particularly in the culinary, beauty, non-formal education, and banking sectors. Data was collected through photographic documentation of signage in eight districts, which was then analyzed based on spatial distribution, language combination forms (monolingual, bilingual, and multilingual), and their socio-cultural functions. The findings reveal that Korean is not only used as a communication tool but also as a symbol of identity and cultural capital in public spaces. The patterns of combining Korean with Indonesian and English reflect marketing strategies, modernity, and symbolic values influenced by globalization and Korean popular culture. These findings confirm that the public spaces of Bandung serve as an arena for interaction between local and global values, reflecting the sociolinguistic dynamics of contemporary urban society.